A microfluidic pump/valve inspired by xylem embolism and transpiration in plants. - Li Jingmin (PLoS ONE, 2012)
In plants, transpiration draws the water upward from the roots to the leaves. However, this flow can be blocked by air bubbles in the xylem conduits, which is called xylem embolism. In this research, we present the design of a biomimetic microfluidic pump/valve based on water transpiration and xylem embolism. This micropump/valve is mainly composed of three parts: the first is a silicon sheet with an array of slit-like micropores to mimic the stomata in a plant leaf; the second is a piece of agarose gel to mimic the mesophyll cells in the sub-cavities of a stoma; the third is a micro-heater which is used to mimic the xylem embolism and its self-repairing. The solution in the microchannels of a microfluidic chip can be driven by the biomimetic "leaf" composed of the silicon sheet and the agarose gel. The halting and flowing of the solution is controlled by the micro-heater. Results have shown that a steady flow rate of 1.12 µl/min can be obtained by using this micropump/valve. The time interval between the turning on/off of the micro-heater and the halt (or flow) of the fluid is only 2∼3 s. This micropump/valve can be used as a "plug and play" fluid-driven unit. It has the potential to be used in many application fields.